Highlights on Hemodynamics - Aslanidis, Theodoros (IntechOpen, 2018)
In the era of functional hemodynamic monitoring and computational modeling, the present book published by IntechOpen® highlights some interesting aspects in the field. Divided into two sections, it presents hemodynamic topics of special interest. Thus, the authors offer the readers not only a "vigorous" review of the current literature but also a research direction for further advancement.